2020
DOI: 10.1155/2020/5736978
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Forest Resource Data Collection Based on Smartphone Fusion with Multiple Sensors

Abstract: Tree parameter measurement is an important part of forest resource monitoring. Smartphones play an important role in forest resource surveys. Although sensors inside smartphones, such as gyroscopes and angle sensors, can meet the needs of the public for entertainment or games, the measurement accuracy in professional forest resource monitoring is slightly insufficient. In this paper, a method of collecting tree measurement factors based on personal smart space fusion with a variety of high-precision sensors is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…Considering the need to protect some resources, it is necessary to effectively ensure the confidentiality and integrity of online education resources. In order to effectively avoid malicious dissemination and disclosure of online education resources, educational resources are collected based on the following principles [ 9 ].…”
Section: Personalized Recommendation Algorithm For Online Education R...mentioning
confidence: 99%
“…Considering the need to protect some resources, it is necessary to effectively ensure the confidentiality and integrity of online education resources. In order to effectively avoid malicious dissemination and disclosure of online education resources, educational resources are collected based on the following principles [ 9 ].…”
Section: Personalized Recommendation Algorithm For Online Education R...mentioning
confidence: 99%
“…Fan et al [23] According to that statement, this paper designs a sensor box for personal smartphones could be integrates with various types of sensors and makes it compact and easy to bind the two to each other. Kafee et al [24] has showed location-based services (LBS) refer to services that account for the realtime, geographic positions of a person or mobile object, as determined by GNSS.…”
Section: Related Workmentioning
confidence: 99%
“…De asemenea, alte studii au vizat analiza impactului social a acestor culturi asupra localităților din proximitate (Coșofreț et al 2016), cât și modul în care acestea contribuie la modificarea proprietăților solului, după o utilizare îndelungată a terenului (Savin et al 2019). Referitor la estimarea producției de biomasă, în practică, există diferite metode care implică măsurători locale sau utilizarea unor surse diferite de date (Dai 2021, Fan et al 2020). Estimarea cât mai precisă a biomasei este o provocare și este necesară pentru planificarea sustenabilă a resurselor forestiere în timp (Bouriaud et al 2015, Naesset et al 2013.…”
Section: Cadru Generalunclassified